(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
To create equitable programmes and services for all children, inclusive early childhood education has increasingly become a major focus of national governments, education systems and schools. Generally, inclusive education has the potential to alter the way society perceives the early education of children. It becomes prudent therefore to explore perceived challenges and gaps experienced by teachers colleges in preparing inclusive early childhood development (ECD) teachers. The study sought to ascertain whether the lecturers in the ECD department are adequately equipped with knowledge, skills and expertise to deal with inclusive education issues. The assumption is that the experiences and expertise will be shared among trained ECD teachers. A qualitative approach employing interviews and document analysis as methods of collecting data was used. Data was collected from one teachers’ college in the Metropolitan province of Harare where two college administrators, 2 lectures lecturers and 5 student teachers were purposively sampled to participate in the study. The research findings revealed that lack of knowledge and skills to deal with inclusive education coupled with unfriendly infrastructure were the major challenges faced by teachers’ colleges. It is therefore recommended that there should be a specific policy to address the implementation of inclusive education in teacher training colleges. More importantly, the infrastructure in teachers’ colleges should reflect inclusivity. Further studies can be undertaken to ascertain the availability of funding and resources in inclusive education in teacher training colleges.